Assessing the global burden of Type 2 diabetes in women of reproductive age. - Juan Luo; Yun Zhang; Zuojie Luo (PLoS ONE, 2025)
This research critically assesses the global prevalence and trends of Type 2 diabetes (T2D) among women of reproductive age (15-39 years) spanning the period from 1990 to 2021. We conducted an analysis of the age-standardized incidence rates (ASIR), Disability-Adjusted Life Years (DALYs), and Estimated Annual Percentage Change (EAPC) using data from the Global Burden of Diseases (GBD) Study 2021. The global ASIR and DALYs per 100,000 among reproductive-aged women increased from 101.01 to 205.17 and from 113.25 to 198.41, respectively. The EAPC for ASIR was 2.32 [95% Confidence Interval (CI): 2.25 to 2.39], and that for DALYs was 1.76 (95% CI: 1.69 to 1.83), both indicating an upward trend. The increase in T2D prevalence was more prominent in the 25-29 age group and younger women. According to Socio-demographic Index (SDI) category, the highest ASIR and age-standardized DALY rate were observed in low-middle SDI regions (ASIR 104.44; age-standardized DALY rate 136.78). The most significant increases in ASIR were recorded in High-income North America (EAPC = 3.64, 95% CI 3.46 to 3.82) and Cameroon (EAPC = 4.30, 95% CI 4.14 to 4.46). In terms of age-standardized DALY rates, the steepest rises were seen in East Asia (EAPC = 2.71, 95% CI 2.34 to 3.08) and Turkmenistan (EAPC = 4.21, 95% CI 3.89 to 4.52). This study shows a remarkable increase in global T2D burden in women of reproductive age between 1990 and 2021. Interventions should be targeted towards women aged 25-29 years and lifestyle risk factors in low-middle SDI, specifically in countries in North Africa and the Middle East, East Asia, Oceania.